STRATEGI MEMBANGUN PERSONAL BRANDING DI ERA DIGITAL BAGI UMKM LOKAL PADA ORKI (OLAHRAGA KEBUGARAN INDONESIA) KOTA TANGERANG SELATAN - Siska Yunanti; Dede Andi; Melda Wiguna (Abdi Jurnal Publikasi, 2025)
The pupose pf this community service activity is to provide sounseling on the Strategy for Building Personal Branding in the Digital Era for Local MSME at ORKI (Indonesian Fitness Sport) Sputh Tangerang City. The methods use in this program include counseling, training and direct assistance to participants. MSME actors are given material on the importance of personal branding, how to create interesting content, and digital marketing strategies to increase customer reach and engagement.in addition, the are also taught how to manage interactions with the audience professionally and build trust through testimonials and customer experiences. Participants are members of the ORKI Community, totaling 24 participants. The result of this activity show an increase in participants understanding in building a stronger business identity. Local MSME actors have begin to apply various branding strategies that have been taught, such as consistency in the use of logos, colors, and communication styles on various digital platforms. In addition, they are also more active in utilizing social media as a means of promotion and interaction with customers. The output of this activity is an accredited journal which can later be used as a reference for various parties.